Pharmacokinetics and safety of the antitumor drug everolimus in healthy Chinese subjects: a single-dose, open-label, randomized, two-sequence, two-period crossover, phase I bioequivalence study - Chen, Xiaodan; Yi, Xiaoyi; Liu, Yuting; Wang, Xiaosong; Peng, Yahui; Wang, Qiong; Shuai, Ying; Zhang, Hong (Frontiers in Pharmacology, 2025)
PurposeIt aims to evaluate the pharmacokinetic (PK) similarity and safety of everolimus in whole blood under fasting and postprandial conditions and its generics in Chinese healthy subjects.MethodsHealthy subjects were enrolled in a single-dose, open-label, randomized, two-sequence, two-period crossover study (Clinical trial registry number: CTR20220446) under fasting and postprandial conditions. The blood concentration of everolimus was quantified by a validated and robust liquid chromatography-tandem mass spectrometry (LC-MS/MS) method.ResultsAll 90% CIs for the geometric mean ratios of Cmax, AUC0-t, and AUC0−∞ were within the bioequivalence range of 80.00%–125.00%. the maximum intra-individual CV% of variation were 22.76% and 18.63% under fasting and fed conditions, respectively. The gastrointestinal absorption rate was decreased by food intake: median Tmax was 0.75 h in the fasted state, and 3.00 h after a high-fat meal. The average elimination half-life (t1/2β, 37.19–38.43 h) and mean residence time (MRT, 23.13–25.81 h) did not appear to be affected by food intake regardless of fasting or fed state. In this study, no serious AE (SAEs) were observed throughout the trial.ConclusionThe systemic availability of a single oral 5 mg dose of everolimus is significantly reduced by coadministration with fed compared with fasting conditions, the test formulation (T) and the reference formulation (R) were bioequivalent.Clinical Trial Registrationclinicaltrials.gov, identifier CTR20220446, (http://www.chinadrugtrials.org.cn/clinicaltrials.searchlist.dhtml).